ANALISIS PENGARUH PEMBELAJARAN DARING TERHADAP PEMAHAMAN MATERI AKUNTANSI DIKALANGAN MAHASISWA AKUNTANSI UNWIRA - Rekong, Karolina; Briand Christofer Wongsono; Kresen Tino Lama Tokan; Yohanes Pemandi Lian (Universitas Prof.Hazairin,SH Bengkulu, 2024)
This study investigated the impact of online learning to the understanding of student accounting materialat the Catholic University of Widia Mandira (UNWRAI). Using the qualitative method and in-depth interview of20 students, this study aims to identify the challenges and benefits faced by students when learning online. Theresult, although online learning offers greater flexibility and better access to learning materials, we find thatchallenges such as lack face-to-face interactions with instructors and difficulty understanding the material is stilla major obstacle. Some students report that even though they feel more comfortable learning alone, the lack ofdirect support hamper their ability to understand the complex accounting concept. This study recommendsincreased interactivity of online courses and develops a more fair valuation method to improve students'understanding. This result is expected to provide valuable information to develop more effective accountinglearning strategies.